Learn more about

Refine search

Results (displaying matches 1-50 of 97) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
461.a.461.1 461.a \(y^2 + x^3y = x^5 - 3x^3 + 3x - 2\) $\mathrm{USp}(4)$ 0
597.a.597.1 597.a \(y^2 + y = x^5 + 2x^4 + 3x^3 + 2x^2 + x\) $\mathrm{USp}(4)$ 0
797.a.797.1 797.a \(y^2 + y = x^5 - x^4 + x^3\) $\mathrm{USp}(4)$ 0
841.a.841.1 841.a \(y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + 3x^2 + x + 2\) $G_{3,3}$ 0
1069.a.1069.1 1069.a \(y^2 + (x^2 + x + 1)y = x^5 + x^3\) $\mathrm{USp}(4)$ 0
1091.a.1091.1 1091.a \(y^2 + (x^2 + x + 1)y = x^5 - 2x^3 - x^2\) $\mathrm{USp}(4)$ 1
1109.b.1109.1 1109.b \(y^2 + y = x^5 - x^4 - x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
1231.a.1231.1 1231.a \(y^2 + (x^3 + 1)y = -x^4 + 2x^2 - x - 2\) $\mathrm{USp}(4)$ 0
1285.a.1285.1 1285.a \(y^2 + y = x^5 - 2x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 0
1811.b.1811.1 1811.b \(y^2 + x^3y = x^5 + x^4 - x^3 - 3x^2 - x + 2\) $\mathrm{USp}(4)$ 0
1844.c.118016.1 1844.c \(y^2 + (x^2 + x + 1)y = 2x^5 + 8x^3 - 31x^2 + 27x - 8\) $\mathrm{USp}(4)$ 0
1981.a.1981.1 1981.a \(y^2 + y = x^5 + 2x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
2704.b.692224.1 2704.b \(y^2 + (x^3 + x)y = -x^4 - 4x^2 - 4\) $G_{3,3}$ 0
3776.c.241664.1 3776.c \(y^2 + (x^2 + 1)y = x^5 - x^4 + x^3 - 2x^2 + 2x - 1\) $\mathrm{USp}(4)$ 0
3904.d.999424.1 3904.d \(y^2 + (x^2 + 1)y = 2x^5 + 3x^3 + x^2 + x\) $\mathrm{USp}(4)$ 0
4168.a.266752.1 4168.a \(y^2 + (x^3 + x)y = x^3 - 2x^2 + x - 1\) $\mathrm{USp}(4)$ 0
4815.a.14445.1 4815.a \(y^2 + y = -x^6 - 7x^5 - 14x^4 + 21x^2 + 10x + 1\) $\mathrm{USp}(4)$ 0
4925.a.4925.1 4925.a \(y^2 + y = 5x^6 - 5x^5 + 12x^3 + 2x^2 - 5x - 2\) $\mathrm{USp}(4)$ 0
5006.a.320384.1 5006.a \(y^2 + xy = x^5 - 2x^4 + 3x^3 - 2x^2 - x + 1\) $\mathrm{USp}(4)$ 1
5408.a.692224.1 5408.a \(y^2 + (x^3 + x)y = -4x^2 + 4\) $G_{3,3}$ 1
5416.a.173312.1 5416.a \(y^2 + (x + 1)y = x^6 - x^2\) $\mathrm{USp}(4)$ 1
5711.a.5711.1 5711.a \(y^2 + (x^2 + x + 1)y = x^5 + 4x^4 - 2x^2 - x\) $\mathrm{USp}(4)$ 1
6327.a.170829.1 6327.a \(y^2 + (x^3 + x^2 + x)y = -x^3 - 4x^2 - x + 4\) $\mathrm{USp}(4)$ 1
6464.a.413696.1 6464.a \(y^2 + xy = x^6 - 8x^5 + 21x^4 - 18x^3 - x\) $\mathrm{USp}(4)$ 0
7023.b.21069.1 7023.b \(y^2 + y = x^5 - x^4 + 9x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 0
7037.a.7037.1 7037.a \(y^2 + (x^2 + x + 1)y = -x^5 - 2x^4 - 6x^3 + x\) $\mathrm{USp}(4)$ 0
7436.b.475904.1 7436.b \(y^2 + (x^3 + 1)y = -x^5 - 2x^4 + 9x^3 - 2x^2 - x\) $G_{3,3}$ 1
8012.a.64096.1 8012.a \(y^2 + (x^3 + 1)y = x^4 + 2x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 1
8128.b.520192.1 8128.b \(y^2 + xy = x^6 - x^4 - 2x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 0
8332.b.66656.1 8332.b \(y^2 + (x^3 + 1)y = 2x^3 - 2x^2\) $\mathrm{USp}(4)$ 1
8788.b.562432.1 8788.b \(y^2 + (x^2 + x)y = x^6 + x^5 + 3x^4 + 2x^3 + 3x^2 + x + 1\) $G_{3,3}$ 1
8936.a.571904.1 8936.a \(y^2 + (x + 1)y = -4x^5 - 4x^4 - 2x^3\) $\mathrm{USp}(4)$ 0
9502.a.608128.1 9502.a \(y^2 + (x^3 + x)y = x^5 - 3x^4 + x^3 - x + 1\) $\mathrm{USp}(4)$ 1
9596.a.614144.1 9596.a \(y^2 + (x^3 + 1)y = x^3 - 4x^2 + 4x - 2\) $\mathrm{USp}(4)$ 0
9848.a.315136.1 9848.a \(y^2 + (x + 1)y = x^6 - 2x^5 - x^4 + x^3\) $\mathrm{USp}(4)$ 1
10468.a.83744.1 10468.a \(y^2 + (x^3 + 1)y = x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 1
10756.a.688384.1 10756.a \(y^2 + (x^2 + x)y = x^5 - 2x^4 + 4x^2 - 6x + 4\) $\mathrm{USp}(4)$ 0
10816.g.86528.1 10816.g \(y^2 + (x^3 + x)y = -3x^4 + 8x^2 - 8\) $G_{3,3}$ 1
10816.h.86528.1 10816.h \(y^2 + (x^3 + x)y = 2x^4 + 8x^2 + 8\) $G_{3,3}$ 0
10824.b.692736.1 10824.b \(y^2 + (x^3 + x)y = -2x^4 - 5x^3 + 15x + 39\) $\mathrm{USp}(4)$ 0
10906.a.697984.1 10906.a \(y^2 + (x^3 + 1)y = x^4 - 2x + 1\) $\mathrm{USp}(4)$ 1
10928.a.87424.1 10928.a \(y^2 + (x + 1)y = -x^6 + 2x^5 - 5x^4 + 5x^3 - 6x^2 + 2x - 2\) $\mathrm{USp}(4)$ 0
11163.a.11163.1 11163.a \(y^2 + y = x^5 + 14x^4 + 51x^3 + 20x^2 - 5x\) $\mathrm{USp}(4)$ 1
11579.a.11579.1 11579.a \(y^2 + y = x^5 - x^4 + 11x^3 + 11x^2 + 3x\) $\mathrm{USp}(4)$ 1
11680.b.747520.1 11680.b \(y^2 + xy = x^6 - 2x^5 + 2x^4 + x^3 - 4x^2 + x + 2\) $\mathrm{USp}(4)$ 0
12086.b.773504.1 12086.b \(y^2 + (x^3 + 1)y = 2x^3 + x^2 - x + 1\) $\mathrm{USp}(4)$ 1
12760.a.816640.1 12760.a \(y^2 + (x^3 + x)y = -x^4 - 6x^3 + 2x^2 + 2x + 34\) $\mathrm{USp}(4)$ 0
12982.a.830848.1 12982.a \(y^2 + xy = x^5 + 2x^4 + 5x^3 + 4x^2 + 3x + 1\) $\mathrm{USp}(4)$ 0
13472.c.862208.1 13472.c \(y^2 + xy = x^6 - 2x^5 - 2x^4 + 5x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 0
14042.a.898688.1 14042.a \(y^2 + xy = x^5 - x^4 + 2x^3 + x + 1\) $\mathrm{USp}(4)$ 1
Next

Download all search results for